從大學的發展趨勢探析十二年國民基本教育普通高中階段的課程改革 From the Development Trend of University to Study High School Curriculum Reform of 12-year Basic Education - 李文富 Wen-Fu Lee (Higher Education Foundation, 2013)
大學階段的人才培育是教育的重要課題，而它與普通高中教育有著密不可分的連動關係。隨著大學數量的擴增、全球化競爭與知識經濟之趨勢，大學教育已從菁英教育朝向大眾化教育，並且人才培育觀也從強調專精專門知識的人才培養轉而強調具備通識、跨領域能力及公民素養的全人教育觀。大學教育的這些轉變與發展，將連動高中教育的定位與課程改革，包括重新定位普通高中的通識教育功能、強化跨領域學科能力、公民素養的培養，以及如何與大學端的優質銜接等。本研究係在此脈絡下，首先說明大學發展趨勢及人才培育觀的轉變，其次探討現行普通高中教育，特別是課程綱要及學校課程在此方面的回應、連動影響與相關現況。最後，則針對未來十二年國民基本教育普通高中階段之課程改革提出若干建議。 The increase in the number of universities has coincided with the growth of international competition in higher education and the development of the global knowledge economy. Universities have responded to these challenges by shifting from an elite view of education to a more popularized model, from prioritizing specialized knowledge to a more holistic emphasis on general knowledge, transdisciplinary skills, and civic literacy. The basic functions of general high school education will have to be reimagined to reflect these developments in university-level education and better links between these two levels will have to be forged. The first part of this paper is an exploration of the changing views of university education. This is followed by a discussion of how the general high school curriculum is evolving in response to these changes. Finally, I offer a number of high school curriculum reform recommendations.